2006
DOI: 10.3164/jcbn.38.167
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-3,5,3',4'-Tetrachlorobiphenyl Induced Membrane Permeability Transition in Isolated Rat Liver Mitochondria

Abstract: Summary Although much information about the apoptotic and other detrimental actions of polychlorinated biphenyls (PCBs) has been accumulated, the critical role of mitochondrial damage in such toxic action remains to be clarified. We have previously shown that PCBs affect various functions in isolated mitochondria. Recent studies have revealed that mitochondria play an important role in apoptosis through membrane permeability transition (MPT), and that Ca 2+ induces classic MPT characterized by depolarization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…52,53,58) These findings indicate that CsA might affect not only pore opening of ANT by binding to cyclophilin D, but also affect the initial steps of MPT, including Ca 2+ transport. 52,59) In our investigation, 54) we observed that 4-OH-TCB disrupts mitochondrial functions as follows: in the presence of Pi and succinate, state 4 respiration increased with increasing concentration of 4-OH-TCB, while the respiratory control and oxidative phosphorylation activity ratios decreased; CsA prevented the effect of 4-OH-TCB on respiration. These results indicate that 4-OH-TCB possibly generates ROS by modulating the electron transport chain in the inner membrane of the mitochondria.…”
Section: Pcbmentioning
confidence: 83%
See 1 more Smart Citation
“…52,53,58) These findings indicate that CsA might affect not only pore opening of ANT by binding to cyclophilin D, but also affect the initial steps of MPT, including Ca 2+ transport. 52,59) In our investigation, 54) we observed that 4-OH-TCB disrupts mitochondrial functions as follows: in the presence of Pi and succinate, state 4 respiration increased with increasing concentration of 4-OH-TCB, while the respiratory control and oxidative phosphorylation activity ratios decreased; CsA prevented the effect of 4-OH-TCB on respiration. These results indicate that 4-OH-TCB possibly generates ROS by modulating the electron transport chain in the inner membrane of the mitochondria.…”
Section: Pcbmentioning
confidence: 83%
“…c from mitochondria. We 54) investigated the effect of the PCB compound, 4-hydroxy-3,3 ,4 ,5-tetrachlorobiphenyl (4-OH-TCB) on isolated rat liver mitochondria to help clarify the effect of PCBs on MPT. We found that 4-OH-TCB enhanced the uncoupling oxidative phosphorylation, the generation of reactive oxygen species (ROS), Ca 2+ release, membrane depolarization, swelling and Cyt.…”
Section: Pcbmentioning
confidence: 99%
“…61) Moreover, our preliminary experiments have shown that 4-hydroxy-3,5,3 ,4 -tetrachlorobiphenyl (4-OH-TCB) enhances T 3 -induced Rana rugosa (R. rugosa) tadpole tail apoptosis in a concentration dependent manner. Recently Fujita et al 62) and Kashiwagi et al 63) reported that 4-OH-TCB induces MPT together with reactive oxygen species (ROS) generation, causing apoptosis.…”
Section: Pcbmentioning
confidence: 99%